(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
We drink without being thirsty and make love at any time that is all that distinguishes us from other animals.BeaumarchaisThe ancient human society was a nomadic society. There was perhaps only a herd-instinct type marital relationship before the dawn of civilization. With the passage of time, the nomadic human beings evolved into an agricultural society and it was considered necessary to ascertain the paternity of children. So long as the sex relationship remained unregulated it was maternity alone, which could be known. Paternity could not be determined. It is logical to say that at some stage of human development the necessity arose for demarcating possession and ownership of material belongings as a natural consequence of human behavior and the human male was seized with the idea of knowing his children. This was not possible if sex promiscuity continued to be the rule. If sex relationship could be made an exclusive union of one man and one woman, only then it was possible to determine the paternity of children. Thus, it seems, in man’s quest to know the paternity of children laid the seeds of the institution of marriage.[1] Thus the concept of marriage is a sort of man-woman relationship as a responsible one-to-one unit of society-evolved a unique human family system. It’s essential components were intercourse, procreation of children and living together with mutual obligations and responsibilities to the care of offspring. The traditional Hindu family was an institution, a joint family system, characterized by homogeneous togetherness of parents, grandparents, sons and daughters, their spouses, even uncles and aunts. There was a distinct family identity with each member knowing his or her roots. The institution of marriage gives respectability to women, enhances their personal happiness welfare, and provides family support companionship.Alas, now a day, family is becoming just an individualistic conjugal family, not even aware of its roots. From times immemorial, Hindus have tried to idealize and sanctify the institution of marriage as no other civil society has done so far. Conjugal fidelity is regarded as the supreme virtue of a woman and it is this character that has protected the Hindu race and Hindu religion down the ages. Purity of the soil and the seed–the sperm and the ovum–alone contributes to the purity of a race and it is with this end in view that so much stress has been laid in our scriptures on the chastity and fidelity of women. Alas This bedrock of human society as a whole and of Hindu society in particular, is under threat from civilization onslaughts from various sources in modern India.